Students’ Experiences in Developing Presentation Skills through Project-Based Learning in the Merdeka Curriculum - Maulidyani AM; Chairil Anwar Korompot; Amra Ariyani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This study aims to explore and provide an in-depth description of students’ experiences in developing presentation skills through Project-Based Learning (PjBL) in the Merdeka Curriculum. A qualitative descriptive research design was employed, enabling the researcher to comprehensively delve into the subjects’ meanings, perceptions, and retrospective accounts. The study involved four Grade XI students from Athirah Islamic School Makassar, selected via purposive sampling to ensure diversity in English proficiency levels and learning experiences. Data were collected through in-depth interviews. The collected data were analyzed using Braun & Clarke’s (2006) reflexive thematic analysis. The findings indicate that, according to students’ reports, the implementation of PjBL provided them with positive, meaningful, and contextual learning experiences. Despite facing challenges—such as limited English vocabulary and grammar mastery, time management difficulties, and technical issues in material preparation—the students perceived that they successfully overcame these obstacles through solid teamwork and constructive teacher guidance. Students further reported perceived improvements across various aspects of presentation skills: self-confidence, speaking fluency, material delivery structure, use of visual aids, body language, and the ability to answer audience questions. The study concludes that students considered PjBL relevant and supportive in developing their communication competence within the Merdeka Curriculum framework.